Elbow Arthrodesis in Twelve Dogs - Haan, J. J. de; Roe, S. C.; Lewis, D. D.; Renberg, W. C.; Kerwin, S. C.; Bebchuk, T. N. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Clinical results of unilateral elbow arthrodesis were retrospectively reviewed in 12 dogs. Variables evaluated included signalment, indications for arthrodesis, surgical technique, elbow angle following the operation, complications, and final functional outcome. The elbow joint should be rigidly immobilized ideally using a bone plate applied to the caudal aspect of the humerus and ulna. The optimal angle of the elbow following arthrodesis appears to be 130° to 140°. Elbow arthrodesis is a salvage procedure, which can result in acceptable function of the limb, but mechanical lameness, due to inability to flex and extend the joint, remains in all animals that have undergone the operation.Clinical results of unilateral elbow arthrodesis were retrospectively reviewed in twelve dogs. Results indicated that the elbow joint should be rigidly immobilized at an angle of 130° to 140°, ideally using a bone plate applied to the caudal aspect of the humerus and ulna. Elbow arthrodesis is a salvage procedure, which can result in acceptable function, but abnormal gait remains in all dogs.
Keywords: Elbow; arthrodesis; dogs